Fuerzas armadas y sociedad - Moncayo Gallegos, Paco, 1940- (Biblioteca de ciencias sociales (Quito, Ecuador), 1995)
"Begins with a historical account of international conflict and the need for national defense. Then discusses the armed forces in Latin America. Concludes with a specific description of the role of the armed forces in Latin America, and in Ecuador in particular. Projects potential roles armed forces could play in the future, such as supporting human rights or protecting the environment"--Handbook of Latin American Studies, v. 57.